Spinal cord meningioma in a Boxer breed dog - Stagnares, Juan J. D.; Pachamé, Andrea V.; Sánchez, Hilda L.; Portiansky, Enrique L. (Brazilian Journal of Veterinary Pathology, 2020)
Meningiomas are one of the most common primary tumors of the canine central nervous system. They usually grow within the cranial cavity but occasionally they are found in the spinal cord. A case of a Boxer breed with a spinal cord transitional meningioma is reported. Two years history presenting progressive neurological signs is described. The MRI examination revealed a focal, intradural extramedullary lesion within the right side of the spinal canal, compromising the C1 and C2 vertebral segments. Cytoreductive surgery with a dorsolateral laminectomy approach was performed to decompress the spinal cord and to obtain a definitive diagnosis. Histopathological studies diagnosed a grade I transitional meningioma. Immunohistochemistry and immunofluorescence analysis detected positive cells to vimentin (VIM), pan-cytokeratin (pCk), neuron-specific enolase (NSE), glial fibrillary acidic protein (GFAP) and doublecortin (DXC). Although apparently benign, positivity to pCK and DXC suggest a possible transition into a malignant tumor. Although variations in the behavior, histology and the immunoreactive profile of these tumors are reported, the latter constitutes a good indicator for the diagnosis of the patient.